Epidemiology of osteoporotic hip fractures in Spain - Herrera, Antonio (Springer-Verlag, 2005)
We conducted a multicentre study, divided into a retrospective and a prospective portion. The retrospective study evaluated osteoporotic hip fractures that occurred during 2002. The prospective study evaluated osteoporotic hip fractures that occurred during May 2003. The study was conducted in 77 hospitals in Spain and comprised patients 60 years of age and over. In the retrospective study we registered 13,195 hip fractures. Of the patients, 74% were women and 26% were men. The mean age was 80.7±8.4 years. The average incidence was 6.94±0.44 hip fractures per 1,000 inhabitants/year (95% CI, 6.07–7.82). In the prospective study, we registered 1,399 hip fractures. This represents a monthly incidence of 0.60±0.04 hip fractures per 1,000 inhabitants/year (95% CI, 0.51–0.69). Of the subjects, 74% were women and 26% were men. The mean age was 81.4±8.1 years. Using these data, we calculated the average annual prevalence in 2003 to be 7.20 fractures per 1,000 inhabitants. Thirty-three percent had previously suffered a hip fracture. Prior to the fracture, only 18% had received medical treatment for osteoporosis. After discharge from the hospital, only 26% were receiving pharmacological treatment for osteoporosis.